Allelopathic Effects of Chrysanthemoides monilifera subsp. monilifera on Lolium rigidum in Wheat Field: Implications on the Reduction of Chemical Loads in Agro-Ecosystems - Harun, M. A. Y. A.; Johnson, Joshua; Uddin, M. N.; Robinson, R. W. (Frontiers in Agronomy, 2021)
Weed control through allelopathic plants is a promising approach that may minimize many of negative consequences of synthetic herbicides. We have studied potential of Chrysanthemoides monilifera subsp. monilifera (boneseed) leaf extract for controlling growth of Lolium rigidum (annual ryegrass) in wheat (Triticum aestivum) fields. Both pre‒and post‒emergent ryegrass‒control experiments were conducted in greenhouse using field soil. Treatments such as boneseed leaf extracts (5% and 10% for pre‒emergent and 10% and 20% for post‒emergent experiments) alone or as a mixture combined with different strength (¼ and ½ strength) of pre‒emergent (boxer gold) and post‒emergent (hussar OD) herbicides were applied on pre- and post‒emergent ryegrass and wheat. The findings revealed that none of the boneseed leaf extracts alone or as mixture had significant inhibitory impact on pre‒emergent ryegrass compared with herbicide alone. Although we observed significant inhibitory impacts on post‒emergent ryegrass with boneseed leaf extracts alone (10% and 20%) compared with control, they were negligible compared to full strength herbicides. Mixtures had significant inhibitory impact on post‒emergent ryegrass compared with herbicide alone with same doses and impact increased with herbicide concentration. Despite the greater impacts by higher herbicides concentration alone, findings suggest the use of mixture of ¼-strength herbicide and 10% boneseed leaf extract was able to control ryegrass successfully than the herbicide alone without adverse impacts on wheat. This study suggests that use of boneseed leaf extract mixed with lower doses of post‒emergent herbicides may be effective in controlling ryegrass with concomitant reductions in expenses and ecological health risks linked with the practice of synthetic herbicides.